Chemical weathering evidence for East Asian Summer Monsoon rainfall variability in the upper reaches of the Yellow River since the Early Pleistocene - Li, Baofeng; Feng, Qi; Wang, Fei; Li, Zaijun; Wang, Xin; Li, Ruolin; Chen, Weiyu (Palaeogeography, palaeoclimatology, palaeoecology, 2023)
The East Asian Summer Monsoon (EASM) is critically important for determining the spatial variability of precipitation in the continental interior of East Asia. Hence, knowledge of past EASM variability may help predict the response of monsoon rainfall to ongoing global climate change, with important implications for the living environment of the large human population of East Asia. In this study, we obtained several geochemical records from the Hetao Basin in the upper reaches of the Yellow River (UYR), which we use to reconstruct variations in chemical weathering intensity since 1.68 Ma. Our results suggest that chemical weathering was significantly intensified during the interval of ∼0.47–0.18 Ma, evidenced by lower Rb/Sr and αAlSr values, and higher LEF Mg/Al values, within the lacustrine sediments during this period. This enhanced chemical weathering was closely linked to increased monsoon rainfall associated with a strong EASM. The long-term trends of EASM rainfall in the UYR were caused by variations in the atmospheric circulation over the Pacific Ocean, such as the ENSO cycle and the PDO phase transition, which may act as testable factors in the prediction of future EASM rainfall. •Long-term monsoon rainfall variation was evidenced by chemical weathering index.•Interglacial East Asian Summer Monsoon was strong from ∼0.47 to ∼0.18 Ma.•Pacific SST gradients play crucial roles in monsoon rainfall patterns in East Asia.